THE INFLUENCE OF PUBLIC SPEAKING IN GETTING A JOB FOR THE ALUMNI OF THE ENGLISH DEPARTMENT OF SRIWIJAYA STATE POLYTECHNIC - Zakaria; Sita Maimunah; Darmaliana; Munaja Rahma (Politeknik Negeri Sriwijaya, 2022)
This research was conducted to find out whether public speaking influenced the alumni of English Department of Sriwijaya State Polytechnic in getting a job or not. The purpose was to know the influence of public speaking towards it. Quantitative method was used by comparing the score of alumni’s public speaking. The population were the alumni of English Department, Sriwijaya State Polytechnic in 2019 and 2020. There were 86 participants answering the questionnaires and 60of them met as the sample criteria.The data were collected by using readymade questionnaire.The resultshowed that there was a positive and significant influenced of public speaking in getting a job for the alumni of English Department, Sriwijaya State Polytechnic . In conclusion, the better a person’s public speaking skill, the higher opportunity of that person in getting a job. This is supported by the results of the answers from the questionnaires that revealed the influence of public speaking in getting a job for the alumni of English Department of Sriwijaya State Polytechnic reaching 85,04%. The result of the questionnaires was also supported by the percentage of public speaking score owned by 60 respondents with the total percentage was 86%. Keywords: English department, getting job, public speaking.